Sequential CAR T-Cell Therapy After Autologous Stem Cell Transplantation for the Treatment of Relapsed/Refractory Intravascular Large B-Cell Lymphoma With Central Nervous System Involvement: A Case Report - Liu, Wanying; Li, Chunrui; Cao, Yang; Wang, Na; Huang, Liang; Shang, Zhen; Wang, Jue; Huang, Lifang; Xu, Jinhuan; Xiao, Min; Zhang, Yicheng; Zhou, Jianfeng; et al. (Frontiers in Oncology, 2022)
Background: Intravascular large B-cell lymphoma (IVLBCL) is a rare, aggressive, large B-cell non-Hodgkin's lymphoma. The prognosis of IVLBCL in patients with central nervous system recurrence after first-line chemotherapy treatment is extremely poor. Among immunotherapies, chimeric antigen receptor (CAR) T-cell immunotherapy has been recently found to be a highly effective treatment for B-cell lymphoma, especially for relapsed or refractory diffuse large B-cell lymphoma. However, no guidelines are available that provide a clear consensus regarding the management of patients with relapsed/refractory IVLBCL. Here, we report, for the first time, the use of autologous hematopoietic stem cell transplantation (ASCT) and CAR T-cell therapy in a patient with relapsed/refractory IVLBCL. Case presentation: A 42‐year‐old woman was diagnosed with IVLBCL based on liver biopsy and developed central nervous system (CNS) recurrence. The patient received ASCT combined with murine monoclonal anti-CD19 and anti-CD22 CAR T-cell therapy. She achieved complete remission for 22 months so far with negative minimal residual disease and continues to be followed up. Conclusion: ASCT combined with CAR T-cell therapy was the best choice for treatment of relapsed/refractory IVLBCL, as it allowed the achievement of a lasting complete remission.